The Role of Communal Wastewater Treatment Plants (WWTP) in Domestic Waste Management: Technology, Construction, Environmental Impact, and Community Participation - Rosalinda Noviyanti Hasugian (Journal Health of Indonesian, 2025)
Communal Wastewater Treatment Plant (WWTP) is a domestic wastewater management system designed to serve several households in one community. The goal is to treat domestic liquid waste centrally so that it is safe for the environment. Communal WWTP is very important, especially in dense residential areas that cannot be served by individual or centralized wastewater treatment systems. This wastewater treatment process involves pipelines connected to storage tanks and wastewater treatment units built according to technical standards to prevent leakage and environmental pollution. Domestic liquid waste, such as greywater and blackwater, which is not properly treated can have negative impacts, including health problems, environmental degradation, and aesthetic damage. Therefore, community participation in the planning, construction, and maintenance of communal WWTP is very important. Active community participation can increase awareness of sanitation, improve environmental management, and support the sustainability of the WWTP system.